Age-related High-frequency Hearing Loss Is Not Associated With Horizontal Semicircular Canal Function. Issue 6 (18th October 2022) - Schubert, Nick M. A.; Roelofs, Catelijne G.; Free, Rolien H.; Wiersinga-Post, J. Esther C.; Pyott, Sonja J.
Abstract : Objective: Investigate the association between age-related hearing loss and reduced peripheral vestibular function using paired assessments of high-frequency hearing and horizontal semicircular canal (HSC) function. We hypothesized that age-related high-frequency hearing loss would be correlated with reduced HSC function and, therefore, useful to predict age-related vestibular hypofunction. Design: We conducted a single center, retrospective cross-sectional study in a tertiary/academic referral hospital. This study included 185 patients who were diagnosed with a cerebellopontine angle (CPA) tumor and referred to the academic hospital to evaluate treatment options. Data collected included pure-tone audiometry, caloric reflex test, video head-impulse test (vHIT), and medical history. High-frequency hearing loss was quantified by the high Fletcher index (hFI), and horizontal semicircular canal (HSC) function were quantified by the caloric reflex test and vHIT. Results: We observed a significant association between age and high-frequency hearing loss that was significantly worse in men compared with women. In contrast, we observed no significant association between age and HSC function assessed by either the caloric reflex test or vHIT. We observed associations between HSC function and sex, with male sex predicting reduced HSC function by caloric reflex testing but enhanced HSC function by vHIT. High-frequency hearing loss did not predict HSC hypofunction. Conclusions: We found no evidence indicating age-related decline in HSC function or an association between age-related high-frequency hearing loss and age-related decline in HSC function. We did observe sex-specific differences in HSC function. Our study highlights the need for sex-specific normative values for identifying age-related reduced peripheral vestibular function and for future work linking comprehensive assessments of inner ear function with tests of balance and stability to understand the complex interactions underlying hearing loss and imbalance, especially in the elderly.